NILAI MORAL FILM PINTU SURGA TERAKHIR, FAJAR BUSTOMI DAN PEMBELAJARAN SASTRA DI SMA - Nissa Ayu Salsabila Nissa; Irwan Baadilla (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This study aims to (1) describe the moral values contained in Pintu Surga Terakhir film by Fajar Bustomi (2) describe the implications of moral values in Pintu Surga Terakhir film by Fajar Bustomi into the learning of literature in high school. This study uses a qualitative descriptive method, which describes the moral values contained in Pintu Surga Terakhir film by Fajar Bustomi. Data collection techniques were carried out through observing techniques and note-taking techniques. The data analysis technique of this research uses data reduction, data presentation, and conclusion drawing. Based on the findings and results of the analysis carried out on this film, it is known that the film Pintu Surga Terakhir contains forms of moral values. These forms of moral values include: empathy, conscience, self-control, respect, kindness. The findings from this study are related to implications for learning literature in high school. Literature learning can be taught in class XI SMA at KD 4.18, it is hoped that it can be useful and add to students' insights about moral values in everyday life. Keywords: Moral Values, Film, Literature Learning in High School